Expression of selected mitochondrial genes during in vitro maturation of bovine oocytes related to their meiotic competence - Němcová, Lucie; Hulínská, Pavlína; Ješeta, Michal; Kempisty, Bartosz; Kaňka, Jiří; Machatková, Marie (Theriogenology, 2019)
The main goal of this study was to characterize the expression patterns of genes which play a role in mitochondrial DNA biogenesis and metabolism during the maturation of bovine oocytes with different meiotic competence and health. Meiotically more and less competent oocytes were obtained separately either from medium (MF) or small (SF) follicles and categorized according to oocyte morphology into healthy and light-atretic. The four oocyte categories were matured and collected after 0, 3, 7, 16 and 24 h of maturation. Either total RNA or poly(A) RNA were extracted from oocytes and the expression of selected mitochondrial translational factors (TFAM, TFB1M, and TFB2M), MATER, and Luciferase as external standard was assessed using a real-time RT-PCR. The level of TFAM, TFB1M and MATER poly(A) RNA transcripts significantly decreased during maturation in both healthy and light-atretic MF and SF oocytes. On the other hand, the level of TFB2M poly(A) increased during maturation in healthy and light-atretic SF oocytes, in contrast to MF oocytes. The abundance of TFAM total RNA was significantly higher after maturation than that before maturation in all oocyte categories. However, no differences in TFB1M and TFB2M total RNA were found in any oocyte categories. It can be concluded that the gene expression patterns differ in maturing bovine oocytes in dependence on their meiotic competence and health. The TFAM and TFB1M poly(A) RNAs are actively deadenylated at different meiotic stages but TFB2M poly(A) RNA remains elevated in light-atretic less competent oocytes until the completion of meiosis.
Keywords: Cattle; Animals; skot; Female; Gene expression; Maturation; Mitochondria; DNA, Mitochondrial; IVM techniky; Oocyte; ženské pohlaví; Oocytes; Genes, Mitochondrial; oocyty; mitochondriální proteiny; In Vitro Oocyte Maturation Techniques; Bovine; mitochondriální geny; mitochondriální DNA; Mitochondrial Proteins; zvířata